QUALITY OF MAKING LESSON PLANS BY SENIOR HIGH SCHOOL TEACHERS IN SIAK REGENCY - Mustafa, M. Nur; Hermandra, Hermandra; Zulhafizh, Zulhafizh (Proceeding of International Conference on Islamic Education (ICIED); Vol 5 No 1 (2020): Proceeding of International Conference on Islamic Education (ICIED), 2021)
This study aimed to find out and to analyze quality of lesson plans by senior high school teachers in Siak Regency. The lesson plans designed by teachers of the schools function as a guideline for them to run teaching and learning process at schools. It is a descriptive research. Data of this study were collected through an instrument filled out by 142 respondents. They were senior high school teachers in Siak regency. Data analysis was presented through descriptive statistics. The research findings revealed that quality of making lesson plans of senior high school teachers in Siak regency belong to the very high category (4.304 or 86.10%). The lesson plans aimed to match teaching material with predetermined competencies, allocate time effectively and efficiently, decide media/tools as well as teaching materials, describe learning objectives and in detail, decide assessment techniques in accordance with the demands of the curriculum, organize teaching materials based on sequences and groups, decide appropriate teaching methods, design learning procedures in accordance with competencies required, and decide appropriate references (textbooks, modules, computer program and so forth) to be used. These findings show that making a lesson plan requires creativity and pedagogical skills. Creativity and motivation lead to positive action in presenting quality, realistic, and concrete lesson plans